Spatio-temporal structural evolution of the Kohat fold and thrust belt of Pakistan. (April 2021) - Ghani, Humaad; Sobel, Edward R.; Zeilinger, Gerold; Glodny, Johannes; Irum, Irum; Sajid, Muhammad
Abstract: The Kohat fold and thrust belt in Pakistan shows a significantly different structural style due to the structural evolution on the double décollement compared to the rest of the Subhimalaya. In order to better understand the spatio-temporal structural evolution of the Kohat fold and thrust belt, we combine balanced cross sections with apatite (U–Th-Sm)/He (AHe) and apatite fission track (AFT) dating. The AHe and AFT ages appear to be totally reset, allowing us to date exhumation above structural ramps. The results suggest that deformation began on the frontal Surghar thrust at 15 Ma, predating or coeval with the development of the Main Boundary thrust at 12 Ma. Deformation propagated southward from the Main Boundary thrust on double décollements between 10 Ma and 2 Ma, resulting in a disharmonic structural style inside the Kohat fold and thrust belt. Thermal modeling of the thermochronologic data suggest that samples inside Kohat fold and thrust belt experienced cooling due to formation of the duplexes; this deformation facilitated tectonic thickening of the wedge and erosion of the Miocene to Pliocene foreland strata. The spatial distribution of AHe and AFT ages in combination with the structural forward model suggest that, in the Kohat fold and thrust belt, the wedge deformed in-sequence as a supercritical wedge ( 15-12 Ma), then readjusted by out-sequence deformation ( 12-0 Ma) within the Kohat fold and thrust belt into a sub-critical wedge. Highlights: Exhumation of the MBT was underway by at least 12 Ma. Thrust front of the Surghar Range of Pakistan Himalaya has been an active structures since 15 Ma. Development of duplexes between the décollements controlled exhumation pattern across the Kohat fold and thrust belt. Out-of-sequence deformation is active today in the interior of the Kohat fold and thrust belt.